Oridonin synergizes with Nutlin-3 in osteosarcoma cells by modulating the levels of multiple Bcl-2 family proteins - Xiao-Hui Wang; Shu-Feng Zhang; Jun-Tao Bao; Fu-Yun Liu (Tumor Biology)
The small-molecule inhibitors of p53–murine double minute 2 interaction, such as Nutlin-3, are effective against cancers bearing wild-type p53. However, murine double minute 2 inhibitors often are unable to completely eliminate solid tumor cells. To address this issue, we investigated the anticancer effects of Nutlin-3 in combination with Oridonin in osteosarcoma cells. We found that Oridonin at sub-toxic concentrations synergistically enhanced Nutlin-3-mediated cell viability inhibition in wild-type p53 U2OS and SJSA-1, but not in p53-mutant MNNG/HOS and in null-p53 Saos-2 osteosarcoma cell lines. Importantly, in the presence of Oridonin, Nutlin-3 could completely abolish cell viability in the wild-type p53 osteosarcoma cell lines. Western blotting analysis showed that Oridonin treatment rapidly and distinctly increased the levels of all three forms of Bim and also markedly reduced the levels of Bcl-2 and Bcl-xl in osteosarcoma cells. Western blotting analysis further showed that Oridonin considerably enhanced Nutlin-3-triggered activation of caspases-9 and -3 and poly(ADP-ribose) polymerase cleavage. Flow cytometry assay showed that Oridonin significantly enhanced Nutlin-3-mediated apoptosis in wild-type p53 osteosarcoma cells. Overall, our results suggest that the combined treatment of Nutlin-3 plus Oridonin may offer a novel therapeutic strategy for osteosarcoma.